Preparation and lithium storage properties of poly (Schiff base)/carbon nanotubes composites - HU Xiu-ying; MAO Chong-chong; HE Chang; CAO Zhi-xiang; DING Yi-ming; BAO Ke-yan (Cailiao gongcheng, 2021)
In order to solve the problem of capacity reduction of Schiff base monomer in lithium-ion batteries due to the dissolution of active substances, the Schiff base polymer(PI) with C=N bond was prepared by one-step condensation method using p-benzaldehyde and p-phenylenediamine as raw materials. Poly(Schiff base)/carbon nanotubes(PI/CNTs) composites with high conductivity were prepared by doping carbon nanotubes(CNTs). The composition, structure, micro morphology and electrochemical properties of the prepared materials were analyzed by using FT-IR, SEM, XRD, TG, XPS and electrochemical workstation. The results indicate that the PI/CNT material with 5%CNTs(mass fraction) is a three-dimensional frame structure, and shows excellent electrochemical performance. The first specific capacity of PI/CNT-3 material is 209.9 mAh·g-1. After 200 cycles, the cycle retention rate is 60.5%. When the rate of charge and discharge is 0.1 C, 0.2 C, 0.5 C, 1 C and 0.1 C, the specific capacity of PI/CNT-3 electrode materials is 182.4, 150.8, 129.8, 101.3 mAh·g-1 and 156.4 mAh·g-1 respectively, which has good cycle stability and rate performance.